The Feasibility of Learning Macromedia Flash 8 Multiple Intelligences Class IV Elementary School - Masruriyah, Jois Syahadati; Istiningsih, Galih (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
This research is motivated by the lack of students' mathematical communication in learning mathematics, especially in the length material unit. In addition, this research was conducted to determine the feasibility of a learning media, namely